HEALTH RELATED QUALITY OF LIFE: CHRONIC KIDNEY DISEASE DENGAN HEMODIALISA MENGGUNAKAN INSTRUMEN EQ-5D-5L DI PEKANBARU - Tiara Tri Agustini; Tri Murti Andayani; Ferdy Firmansyah (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
Chronic Kidney Disease (CKD) is a kidney disorder that continues to increase the globally and its also irreversible. Hemodialysis (HD) performed by CKD patients with severe conditions. Quality of life is one indicator of the success therapy patients CKD with HD. In addition to clinical conditions, the characteristics of patients can be affected to the quality of life. The aims of this study is to see the effect of the characteristics of CKD with HD of the Score Index utility. Its were measured using the EuroQuality of 5-dimensional 5 levels (EQ-5D-5L). The study was performed with the observational conversion using a cross sectional design in the CKD population in Pekanbaru hospital. The EQ-5D-5L questionnaire is given to 122 patients to measure the score utility. Different index score utility based on the characteristics of the tested patients using Mann Whitney and Kruskal Wallis. Based on the study, the average value of Pasa Pasa patients with HD patients was 0.24 ± 0.27. Dimensions of anxiety / depression and pain / discomfort of 6.56% with very severe problems and 2.46% could not move. Based on the anysis results, there are differences in utility values based on age characteristics, education levels, and commorbids (p <0.05).